Psychological Antecedents and Consequences of Social Integration Based on Self-Disclosure in Virtual Communities: Empirical Evidence From Sina Microblog - Zhang, Yixin; Cheng, Zhichao; Pan, Yue; Xu, Yiwen (Frontiers in Psychology, 2022)
With the normalization of COVID-19 prevention and control, a large number of intergenerational audiences with different cognition preference and value orientation started to pour into the non-acquaintance virtual communities (VCs) to address their social need by disclosing their own thoughts, feelings and experiences towards certain topics. To avoid the negative impacts of self-disclosure, this study introduced the concept of social integration into the cyber-society among non-acquaintance VCs, such as the topic-based VCs. Our theoretical model considered both psychological antecedents and consequences of VC audiences’ social integration and our findings would have implications for public online and even offline social life. Moreover, this research could play a guiding role in improving VC audiences’ social integration status online learning and telecommuting scenarios in the future.